EVALUASI INSTALASI SISTEM HIDRAN PADA GEDUNG KANTOR PT. PERTAMINA LUBRICANTS JAKARTA UTARA - Annistyaningrum, Lanti; Ekawati, Ekawati; Kurniawan, Bina (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2015)
Nowadays multistorey building are widely spread in almost every city in Indonesia, especially in metropolitan city such as Jakarta. The overuse of electricity in multistorey building has unconsciously remained hazardous potential to trigger fire. One of the prevention act to the fire spreading is by installing the proper hydrant system around the building. In this writings, evaluation regarding to the hydrant building installation refers to a government regulation. PT. Pertamina Lubricants office building is used for office activities and laboratorial test, where the overuse of electricity could trigger another hazardous potential which is chemical hazards that could cause fire. PT. Pertamina Lubricants building has already had hydrant installation with the quantity of 5 hydrant box. The placement and the number of the hydrant box in every stairs hasn’t reached the standard. The evaluation result on the hydrant system of the building and the component completeness has attained the standard with the precentage of 68.2% allowed. Any broken hydrant tools or components are not found in this building, every hydrant parts is in a good condition.